PEMAKNAAN KHALAYAK TERHADAP KEBEBASAN PERS DALAM FILM THE POST - Bela Nagari, Kaninda; Dwiningtyas Sulistyani, Hapsari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
In watching film, the audience actively produces the meaning of the texts in the film. The audience's active interpretation of film texts makes the meanings diverse. This is because each audience has a different background, experience and daily life. The Post is a film featuring press freedom based on United States history. This film presents a picture of the media and newspaper reporters in carrying out their duties when faced with realities on the ground. Reporters are described as not always running smoothly when carrying out their journalistic duties, they are faced with challenges and obstacles both from within the media company and from outside. However, the meaning of the audience is not necessarily in accordance with the meaning offered by the media text in the film The Post. This study aims to describe the audience's meaning of press freedom in the film The Post. This study uses a qualitative-descriptive approach, and the Stuart Hall reception analysis method. The subjects of this research are journalists, press workers and media observers who have watched The Post film. The paradigm of this research is interpretive and the theory used is the Encoding-Decoding Model, Audience Meaning Theory and Four Theories of The Press. This study aims to describe the audience's meaning of press freedom in The Post film. This study uses a qualitative-descriptive approach, and the Stuart Hall reception analysis method. The subjects of this research are journalists, press workers and media observers who have watched The Post film. The paradigm of this research is interpretive and the theory used is Four Theories of The Press, Audience Meaning Theory, and Encoding-Decoding Model. The results of this study succeeded selected sixteen preferred readings that featured press freedom in the text in The Post film. From the results of the research, it shows that the informants have different meanings. However, on the whole, informants have a tendency to interpret media texts in a negotiation. Informants interpret media texts in a negotiated position on the element of intervention freedom, there are it is natural that there is intervention in the political economy of the media because they think about the impact but if the impact of news is not greater than the interests of the community then there should be no prevention, the redaction does not have to ask the media owner's approval when publishing but in general the redaction ask the media owner's approval, and it doesn't matter the redaction ask for the media owner's approval but the news must contain confirmation from the parties concerned. On element of publication freedom, there are the media are free to publish news but must include sources of information, the sources must be clear and competent, and still refers to journalistic principles and Journalistic Code of Ethics. On element of judicial independence, there is the publication of the Pentagon Papers news does not violate the Espionage Act so it should not be brought to justice. On element of public broadcasting institutions, there are when the news has a large impact then the media people must discuss first not immediately publish news and it doesn't matter the source is the same as other media but the most important thing is different on the presentation. On element of criminalization and intimidation of the press, there are accommodative media are loved and critical media are silenced, censorship is not in accordance with press freedom but the presentation of news must be balanced, news publications can violate the rule of law but from a journalistic perspective it does not violate the rule of law, the rule of law can indeed curb but writing remain accountable, the thought of journalists when writing but in writing remains according to journalistic principles, and news publications remain in accordance to Journalistic Code of Ethics. Informants interpret media texts based on the context and situation of a media as well as from their knowledge and everyday experiences.